Financial, Economic Crisis and Quality in Health Services Provision, New Challenges to Improve Quality Policy in the Healthcare System of Greece - Kountoura, Antonia; Stavros Emmanouil; Efthymios Ziagkas (Technium Social Sciences Journal, 2020)
Greece has been severely affected by the global financial and economic crisis, with far-reaching economic, social and political consequences. In 2013, the country was already experiencing its fifth year of recession and was operating within suffocating tax measures. Prior to the crisis, the Greek healthcare system suffered from a wide range of problems. Therefore, it was vulnerable to economic fluctuations and was not properly prepared to meet the changing needs of the population. The aim of this study was firstly to investigate the effect of the economic crisis on the quality of health care in Greece and secondly to propose methods to improve the quality policy of the Greek Health System. A literature review was carried out in order to collect all available information of the relevant literature sources in both Greek and international English-language bibliography. The effects of the economic crisis on the Greek national healthcare system were recorded extendedly. In particular, the effects of the economic crisis on access to health services, the effectiveness of hospital care, the quality of health care provided, the transparency and oversight are analysed. In summary, the need to re-examine and promote a public debate on the health budget, not only in economic terms, but as a development tool for the well-being of citizens, is emphasized. In conclusion, restoring the social values that govern the health care system is a prerequisite for creating a new model for sustainable development